The home guard a military and political history - Mackenzie, S. P. (Oxford University Press, 1995)
The extraordinarily popular British television program "Dad's Army" suggests that Britain's Home Guard during the Second World War was home to charming incompetence and lighthearted buffoonery. In 1940, however, the threat of a German invasion of Britain appeared very real. S. P. MacKenzie's detailed and readable history of the Home Guard offers a new perspective on the men who took up the challenge. Despite its popular image of old men and teenagers playing soldiers, the Home Guard, often as large as the wartime army, became an astonishingly strong political force in its own right. Quite literally the people in arms, it proved able to exert a good deal of influence on policy. The Home Guard was never called upon to fulfil its military role, though there was a brief attempt to resurrect it in the 1950s. Since then it has been largely neglected by military historians and there have been few serious examinations of the part it played in the Home Front. This book fills that gap.